2015
DOI: 10.1007/s10354-015-0358-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of the first trimester Doppler scan: a meta-study

Abstract: Predictive sensitivity of the UAD increases after 16 weeks + 3 days (115 days) of gestation. The best predictive parameter of preeclampsia and FGR is the placental side uterine artery resistance index which confers to the highest means when the placenta is on the midline (OR 0.9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 75 publications
(89 reference statements)
1
5
0
4
Order By: Relevance
“…Further, a recent meta-analysis showed that the most effective predictive parameter for PE is the placental side UtA RI. [14] However, consistent with the findings of other studies, [2022] our results indicated that placental-side PI can significantly improve the prediction of PE. Nevertheless, our study is the largest study conducted thus far in a homogenous Chinese population for the assessment of the value of placenta-side UtA PI in predicting early-onset PE.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Further, a recent meta-analysis showed that the most effective predictive parameter for PE is the placental side UtA RI. [14] However, consistent with the findings of other studies, [2022] our results indicated that placental-side PI can significantly improve the prediction of PE. Nevertheless, our study is the largest study conducted thus far in a homogenous Chinese population for the assessment of the value of placenta-side UtA PI in predicting early-onset PE.…”
Section: Discussionsupporting
confidence: 92%
“…Traditionally, the PI is measured on the left- and right-side UtAs, and the mean of the 2 measurements is used in the prediction of PE. [14] A previous study has shown that the lowest UtA PI value was the most effective in predicting PE and that it has the best performance. [11] However, in that study, [11] the authors did not specify the placental laterality, assuming that the vessel with the lower PI is likely to be the placental one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several UtA Doppler characteristics have been tested for their ability to predict PE [11,12]. Although the pulsatility index (PI) has typically been assessed in both UtAs and the mean of the two readings is used to predict PE, the lowest UtA PI has been proven to have the greatest predictive value performance [13]. Nonetheless, research on the use of UtA Doppler velocimetry in the prediction of PE has shown varying degrees of sensitivity.…”
Section: Introductionmentioning
confidence: 99%